Characterization of Sunflower (Helianthus annus L.) Genotypes for Some Qualitative Traits at Central Highlands of Ethiopia - Abu, Mohammed (International Journal For Research In Agricultural And Food Science, 2020)
Twenty five sunflower genotypes were characterized for their qualitative morphological traits to detect phenotypic differences present among different sunflower genotypes. the study was conducted during 2017/18 across two location namely, Holetta and Adadi. The trial was laid out using simple lattice design. Eleven qualitative traits data were collected using morphological descriptor. No environmental effect was observed for all traits. Shannon diversity index was used for analysis of variation among genotypes for qualitative traits. All qualitative traits shows variation among genotypes except pollen color, ray floret color and leaf shape. Majority of the genotypes showed elongated ray floret shape (84%), medium leaf serration (48%), medium hairiness at top of stem (68%), erect to semi erect leaf petiole (44%), dropping leaf blade (66%), elongated bract shape (80%) and Concave head shape (72). Half branch was observed in 16% of genotypes while majority of them (84%) have no branches.